Evaluation of various head flexion angles in hippocampal-avoidance whole-brain radiotherapy using volumetric modulated arc therapy. (August 2020) - Lin, Y.F.; Chen, P.H.; Shueng, P.W.; Lin, H.H.; Lai, L.H.
Abstract: Whole-brain radiotherapy (WBRT) with hippocampal avoidance improves neurocognitive function deterioration. To improve both planning and treatment efficiency, we investigated the feasibility of using the coplanar volumetric-modulated arc therapy (VMAT) technique with various head flexion angles for hippocampal avoidance during WBRT. Six patients with brain metastases were selected for the study. We rotated patient CT images by 90° and changed the couch angle to simulate different head flexion angles. The plan with a head angle of 0° had the lowest planning target volume (PTV) coverage and the highest normal organ dose (i.e., hippocampus and bilateral lenses). When the angle was equal to or greater than 15°, the maximum dose of the hippocampus and the PTV V30 met all dose constraints. The results obtained with head angles equal to or greater than 25° were better than those obtained at angles below 25° with the obviously decreased dose of the bilateral lenses. The VMAT treatment plans of each patient were computed under various head flexion angles using the Eclipse Treatment Planning System. The study demonstrated that 15° is the minimum head flexion angle that should be adopted in clinical practice. For better dose coverage and uniformity for whole-brain PTV and dose reduction of critical organs, the study results suggested utilizing a head angle equal to or greater than 25°, while ensuring that patient comfort is maintained with larger head flexion angles. Compared with non-coplanar linac-based techniques, a tilted head angle with the coplanar VMAT technique not only reduces plan complexity but also improves treatment efficiency. Highlights: WBRT with hippocampal avoidance improves neurocognitive function deterioration. The coplanar VMAT with various head flexion angles for HA-WBRT is investigated. A tilted head angle with the VMAT technique improves treatment efficiency.